2018
DOI: 10.1248/bpb.b17-00877
|View full text |Cite
|
Sign up to set email alerts
|

SKF83959 Has Protective Effects in the Scopolamine Model of Dementia

Abstract: Patients with Alzheimer's disease (AD) always have cognitive impairments. In this study we investigated whether 6-chloro-7,8-dihydroxy-3-methyl-1-(3-methylphenyl)-2,3,4,5-tetrahydro-1H-3-benzazepine (SKF83959) has improvements on cognitive dysfunction. The scopolamine model of dementia was used to investigate the anti-amnesic activities of SKF83959, and then, Western blotting and pharmacological inhibitor were used to assay the anti-amnesic mechanisms of SKF83959. It was found that SKF83959 administration sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…were made at the volume of 10 ml/kg of mice body weight, and fresh solutions were prepared every day before administration. The scopolamine LPS and imipramine doses were chosen based on literature data 39 41 and our previous studies 14 . The doses of scoparone (2.5, 5, 12.5, 15, 25 mg/kg) were chosen based on our pilot study and literature data 42 .…”
Section: Methodsmentioning
confidence: 99%
“…were made at the volume of 10 ml/kg of mice body weight, and fresh solutions were prepared every day before administration. The scopolamine LPS and imipramine doses were chosen based on literature data 39 41 and our previous studies 14 . The doses of scoparone (2.5, 5, 12.5, 15, 25 mg/kg) were chosen based on our pilot study and literature data 42 .…”
Section: Methodsmentioning
confidence: 99%
“…Some memory improvement activities have also been demonstrated for benzazepines SKF83959 and SKF38393. For example, administration of SKF83959 significantly improved scopolamine-induced memory impairments in the passive avoidance task, spontaneous alternation test, and place learning task in the Morris water maze task in mice (Sheng et al, 2018; Table 1). SKF38393 has been shown to improve temporal order memory performance in maternally deprived rats (Lejeune et al, 2013; Table 1).…”
Section: Comparison Of the Effects Of Allosteric Sig1r Modulatorsmentioning
confidence: 99%
“…Additionally, all of the above three compounds elicited no significant effect on [ 3 H]-DTG binding to the σ 2 receptor, indicating that they are selective σ 1 receptor PAMs. Further in vivo studies found that the anticonvulsant activity of SKF83959 was attributed to σ 1 receptor modulation and its anti-Parkinson’s, antidepressant, and memory improvement activities were mainly mediated by interactions with dopamine receptors . SKF83959 at doses of 20 and 40 mg/kg demonstrated anticonvulsant effects in PTZ- and kainic acid (KA)-induced seizures models.…”
Section: Small Molecules Selectively Targeting Sigma-1 Receptormentioning
confidence: 95%
“…Further in vivo studies found that the anticonvulsant activity of SKF83959 was attributed to σ 1 receptor modulation and its anti-Parkinson's, antidepressant, and memory improvement activities were mainly mediated by interactions with dopamine receptors. 206 SKF83959 at doses of 20 and 40 mg/kg demonstrated anticonvulsant effects in PTZ-and kainic acid (KA)-induced seizures models. SKF83959 reduced cortical epileptiform activity and did not alter spontaneous motor activity or motor coordination, which are common side effects of current antiepileptic drugs and σ 1 receptor agonists.…”
Section: Small Molecules Selectively Targetingmentioning
confidence: 99%